2007
DOI: 10.1021/jp076382d
|View full text |Cite
|
Sign up to set email alerts
|

Selective Growth of Pure and Long ZnO Nanowires by Controlled Vapor Concentration Gradients

Abstract: ZnO can appear as nanowires, nanobelts, and nanocombs, which are attractive for various applications. However, this has prevented the growth of desired nanostructures without other trace morphologies. Here we demonstrated a mechanism for selective growth of pure and long ZnO nanowires. This was obtained by placing a gold film at a high-temperature zone so that ZnO nanowires with controllable densities can be grown on adjacent bare substrates at lower temperature zones. The concentration gradients of gold and Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 13 publications
0
21
0
Order By: Relevance
“…In this set-up, the full nanowire-contacts system may be regarded as having a pinned and clamped configuration. Our ZnO nanostructured samples were synthesized by the thermal chemical vapor deposition method, as reported elsewhere [22,23]. Figure 2(c) displays the ZnO nanowire under the compressive/bending state by incremental movement of the piezo-driven gold tip against the AFM tip.…”
Section: Methodsmentioning
confidence: 99%
“…In this set-up, the full nanowire-contacts system may be regarded as having a pinned and clamped configuration. Our ZnO nanostructured samples were synthesized by the thermal chemical vapor deposition method, as reported elsewhere [22,23]. Figure 2(c) displays the ZnO nanowire under the compressive/bending state by incremental movement of the piezo-driven gold tip against the AFM tip.…”
Section: Methodsmentioning
confidence: 99%
“…33 Experimental studies using similar equipment have shown that, inside the furnace, the temperature and the ZnO vapor pressure decreases as the distance to the source ͑alumina boat containing ZnO powder͒ increases. [35][36][37] Various morphologies of ZnO nanostructures, with a wide range of aspect ratios, were formed depending on the substrate temperature and distance to the source. [35][36][37] ZnO nanobelts with high w / t were most likely observed on the substrate located close to the ZnO source at a higher temperature, and that observation was made whether a gold catalyst was added to the substrate or not.…”
Section: Resultsmentioning
confidence: 99%
“…[35][36][37] Various morphologies of ZnO nanostructures, with a wide range of aspect ratios, were formed depending on the substrate temperature and distance to the source. [35][36][37] ZnO nanobelts with high w / t were most likely observed on the substrate located close to the ZnO source at a higher temperature, and that observation was made whether a gold catalyst was added to the substrate or not. 37 Growth at high temperatures and large supersaturation ratio ͑nonequilibrium conditions͒ also leads to ZnO nanostructures with a high density of defects, due to the higher deposition rate of molecular ZnO from the vapor.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our ZnO samples were synthesized by thermal chemical vapor deposition method, as reported elsewhere. 9,10 For in situ electrical measurement, an individual ZnO nanobelt was attached to the electromechanically etched tungsten tip by tungsten deposition using the focused ion beam ͑FIB͒ technique to ensure good electrical contact between the tip and the nanobelt. The different steps of the sample preparation are shown in Figs.…”
Section: In Situ Probing Of Electromechanical Properties Of An Indivimentioning
confidence: 99%